The Grammar of Guilt: A Communication Analysis of “Face-Saving” Strategies in Academic Refusals among Undergraduates - Ain Shahruddin; Nena Padilla-Valdez (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2026)
This study investigates the linguistic strategies used by undergraduates to manage the face-threatening act of boundary-setting during refusals. Participants include 25 transient Bruneian undergraduates studying at Universities across Malaysia. Data was systematically gathered via an online questionnaire featuring five Discourse Completion Tasks (DCTs) simulating extracurricular requests across varying social distances. To capture the intersection of emotional stress and linguistic choice, this study introduces the original term “Grammar of Guilt” to define the specific strategy deployed by speakers to manage the internal anxiety of setting personal boundaries. Evaluated through qualitative discourse, thematic, and cross-scenario frequency analysis, the findings revealed that the “Grammar of Guilt” operates as a fluid, context-dependent face management system that is driven by peer equity and vertical power asymmetries. Frequency Variation shows that Justification Buffers serve as the primary structural shield across all scenarios (64.0%-84.0% frequency) as students consistently externalize blame by leveraging institutional deadlines or cognitive exhaustion to avoid social blame. Additionally, politeness obligations plummet when peer equity is breached, as undergraduates enforce accountability by weaponizing the cultural concept of social shame. Furthermore, a gender split emerged where females operate on a binary of emotional overcompensation or rigid boundaries, while males build transactional negotiation bridges using casual peer slang and practical task compromises. Additionally, undergraduates exploit digital platform parameters to bypass real-time confrontation by executing temporal manipulation through strategic ghosting and technological offloading to ChatGPT. Overall, this study refines politeness theory by proving that collective harmony among undergraduates is highly conditional and based on mutual peer effort, while exposing an academic burnout crisis where modern undergraduates must weaponize mental health terminology to protect basic personal autonomy.